Systematic Review: Functional Assessment and Stereotyped Behavior Intervention (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Based on a systematic review of the literature, we sought to identify in the behavioral-analytic publications which procedures were used for the functional assessment of stereotypied behaviors, as well as the intervention strategies used to weaken or interrupt stereotypes. Of the total number of publications identified (n = 247 in Portuguese and n = 261 in English), two national and six foreign publications were included. Thus, the use of functional assessment procedures for the subsequent selection of effective intervention strategies to modify stereotyped behaviors is understood to be fundamental.
Keywords: autism; stereotyped behaviors; functional assessment; intervention strategies.